2012
DOI: 10.2169/internalmedicine.51.7419
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Portal Venous Gas Associated with Severe Graft-versus-host Disease of the Gastrointestinal Tract

Abstract: We report a 67-year-old woman who was diagnosed with hepatic portal venous gas associated with severe graft-versus-host disease (GVHD) of the gastrointestinal tract. The patient received allogenic peripheral blood stem cell transplantation from a haploidentical son against Philadelphia chromosome-positive acute lymphocytic leukemia. The patient developed grade 3 intestinal GVHD on day 90 from the transplantation. On day 149, she presented septic shock and computed tomography (CT) scan revealed hepatic portal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although the presence of gas in the portal venous system was generally considered to be a serious intra-abdominal event, many benign cases have been put forward with the development of imaging modalities. Our search for reported cases of HPVG during the most recent 5 years (table 2 ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] revealed that 20 of the 31 patients were treated by a nonsurgical approach, and 22 (71%) of the 31 patients recovered, suggesting that HPVG is not always a fatal sign in those patients. In addition, invasive therapy, including chemotherapy, endoscopic retrograde cholangiopancreatography, and CT-guided aspiration biopsy, was performed in 14 (45.2%) of the 31 patients before onset of HPVG.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of gas in the portal venous system was generally considered to be a serious intra-abdominal event, many benign cases have been put forward with the development of imaging modalities. Our search for reported cases of HPVG during the most recent 5 years (table 2 ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] revealed that 20 of the 31 patients were treated by a nonsurgical approach, and 22 (71%) of the 31 patients recovered, suggesting that HPVG is not always a fatal sign in those patients. In addition, invasive therapy, including chemotherapy, endoscopic retrograde cholangiopancreatography, and CT-guided aspiration biopsy, was performed in 14 (45.2%) of the 31 patients before onset of HPVG.…”
Section: Discussionmentioning
confidence: 99%